Examining Teacher Retention through the Lens of Job Satisfaction and Commitment in a Philippine Private School - Anog, Maria Domnena Inso; Vera, John Virtucio de; Peteros, Emerson De Luna (International Journal of Learning, Teaching and Educational Research, 2024)
This research explored the relationship between teachers’ school commitment, job satisfaction, and their retention in a private school in Cebu, Philippines during the school year 2023–2024. One hundred and seventeen (117) teachers were selected using random sampling and completed a four-part survey questionnaire assessing their profile, school commitment, job satisfaction, and retention. The statistical measurements used to analyze the data were frequency count, percentage, weighted mean, standard deviation, and Pearson product-moment correlation coefficient. Data reveal that the respondents had a very high degree of school commitment and job satisfaction. Moreover, working conditions had a very high degree of influence on respondents’ retention, while compensation, administrative support, and professional growth had a high degree of influence. Furthermore, school commitment is significantly related to teacher job satisfaction and retention, while job satisfaction is significantly related to teacher retention. These findings suggest that enhancing teachers’ commitment and job satisfaction may be strategic in improving their retention. Therefore, school administrators must promote a positive working environment to foster school commitment, job satisfaction, and retention.